M-learning standardization: concepts and new ideas about learner profile - Anido Rifón, Luis (2006)
The Learning Technology (LT) standardization process is a hot topic today within the e-learning scientific community. This paper introduces the main LT specifications, and, specifically, presents several concepts about Learner Information standards, discussing some complements to them related to mobile learning.